The Transmission of Natural Shocks in the Costa Rican Agricultural Sector and Market Interrelations - Hall, Luis J. (2010)
This paper examines to what extent productivity shocks from different regions within Costa Rica and climate factors explains the volatility observed in productivity and production levels of Costa Rican primary grains, rice, corn and beans, at the regional level. More precisely, The paper evaluates three types of shocks. Productivity shocks from other regions producing these grains within the country, movements in rain levels within the region, and changes in temperature on the sea surface (SSt) as a proxy for the “Niño Effect.” The evidence sheds light initially on the degree of industrial organization within these productive sectors, and also the impact of natural shocks on the agricultural sector. The evidence suggests enormous differences in theorganization of the rice sector as opposed to the bean and corn sectors. the paper also shows how changes in climatic variables, as measured by levels in rain and SSt explain the movements in the productivity of the grain sectors. Rain levels explain roughly 15% to 20% of the total variation in productivity levels of these grains and surprisingly SSt roughly 25%.